2005
DOI: 10.1037/0278-6133.24.2.198
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Components Analysis of Brief Theory-Based HIV/AIDS Risk-Reduction Counseling for Sexually Transmitted Infection Patients.

Abstract: An experimental components analysis of brief HIV risk-reduction counseling based on the information-motivation-behavioral skills (IMB) model was conducted with 432 men and 193 women receiving sexually transmitted infection (STI) clinic services. Following baseline assessments, participants were randomly assigned to 1 of 4 90-min risk-reduction counseling sessions that deconstructed the IMB model within a full factorial design. Participants were followed for 9 months, with STI diagnoses monitored over 12 months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 74 publications
(51 citation statements)
references
References 28 publications
2
47
2
Order By: Relevance
“…34 HIV/STI prevention within jail systems could test brief, even single-session, risk reduction interventions, which have been shown effective in various populations. [50][51][52] Additionally, HIV prevention studies could recruit participants from jail settings and implement prevention interventions upon community reentry-a highrisk window of opportunity for intervention. 53,54 Providing HIV/STI prevention services to non-incarcerated arrestees could be accomplished in community settings such as probation and alternative to incarceration programs.…”
Section: Discussionmentioning
confidence: 99%
“…34 HIV/STI prevention within jail systems could test brief, even single-session, risk reduction interventions, which have been shown effective in various populations. [50][51][52] Additionally, HIV prevention studies could recruit participants from jail settings and implement prevention interventions upon community reentry-a highrisk window of opportunity for intervention. 53,54 Providing HIV/STI prevention services to non-incarcerated arrestees could be accomplished in community settings such as probation and alternative to incarceration programs.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence shows that MI has been applied to a variety of fields including diabetes, asthma, hypertension, heart disease, substance abuse, smoking, HIV risk reduction, diet and exercise. 10,11,[29][30][31][32] Most studies displayed positive results for the effectiveness of MI in altering behaviours. One systematic review found positive results for the effects of MI on psychological, physiological and lifestyle change outcomes 11 and concluded that MI has the potential to be an effective intervention in physical health care settings.…”
Section: Motivational Interviewingmentioning
confidence: 99%
“…15 The IMB Model draws on the tenets of Social Cognitive Theory 49 and Theory of Reasoned Action, 50 and it asserts that the fundamental determinants of engaging in behaviors that prevent HIV acquisition are the combined effects of having: (a) HIV-related information and prevention knowledge, (b) motivation to become/stay safer, and (c) necessary skills to engage in prevention behaviors, including self-efficacy to use condoms. 51 The literature on heterosexual youth and adults generally supports the association between the components of the IMB model and sexual risk behavior in both observational studies 16,[51][52][53][54][55][56] and tests of interventions. 57,58 However, evidence suggests that motivation and behavioral skills may play a more proximal role in influencing sexual risk than HIVrelated information.…”
Section: Information Motivation and Behavioral Skills (Imb)mentioning
confidence: 99%